IMPLEMENTASI DIMMER AC BERBASIS ARDUINO PADA PENGATURAN KECEPATAN MOTOR INDUKSI SATU FASA - Fadhillah hazrina (Universitas Lampung, 2023)
Some things that must be considered to improve the work of an induction motor are the rotational speed of the motor which is expected to continue to be increased, torque that can meet the load, and higher efficiency. Multilevel inverters will play an important role in converting DC energy from battery sources into AC electrical energy. This study aims to create a single-phase induction motor speed control system with an Arduino Mega-based Multilevel inverter. External input in this study uses a normally close push button with two initializations, namely the Up and Down push buttons. The push button functions as an induction motor speed control with speed conversion in the form of a percent parameter. Parameters will appear on the LCD display for every change that occurs. The test results show that the induction motor will start rotating at a percentage of 20%, namely at a speed of 1631.8 RPM, then Up to 40% at a speed of 2260.2, Up again to 60% at a speed 3261.8 RPM, and at 80% speed it produces 4163.8 and the highest speed reaches 5241.4 RPM with a speed percentage of 100%. The rotational speed of the motor can be displayed on the LCD display in the form of a digital display.